Modulation of cell death by Bcl-x(L) through caspase interaction - Clem, Rollie J. (The National Academy of Sciences, 1998)
The caspases are cysteine proteases that have been implicated in the execution of programmed cell death in organisms ranging from nematodes to humans. Many members of the Bcl-2 family, including Bcl-x(L), are potent inhibitors of programmed cell death and inhibit activation of caspases in cells. Here, we report a direct interaction between caspases and Bcl-x(L). The loop domain of Bcl-x(L) is cleaved by caspases in vitro and in cells induced to undergo apoptotic death after Sindbis virus infection or interleukin 3 withdrawal. Mutation of the caspase cleavage site in Bcl-x(L) in conjunction with a mutation in the BH1 homology domain impairs the death-inhibitory activity of Bcl-x(L), suggesting that interaction of Bcl-x(L) with caspases may be an important mechanism of inhibiting cell death. However, once Bcl-x(L) is cleaved, the C-terminal fragment of Bcl-x(L) potently induces apoptosis. Taken together, these findings indicate that the recognition/cleavage site of Bcl-x(L) may facilitate protection against cell death by acting at the level of caspase activation and that cleavage of Bcl-x(L) during the execution phase of cell death converts Bcl-x(L) from a protective to a lethal protein.